Convergence or divergence? Immigrant wage assimilation patterns in Germany - Michael Zibrowius (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2011)
Using a rich German panel data set, I estimate wage assimilation patterns for immigrants in Germany. This study contributes to the literature by performing separate estimations by skill groups and controlling for a wide range of socio-economic background variables. It aims to answer the question whether Germany can be considered an attractive host country from an immigrant's perspective. Comparisons with similar natives reveal that immigrants' experience earnings profiles are flatter on average, although clear differences show up among skill groups. The effect of time spent in the host country is significantly positive for all skill groups and thus partly offsetting the diverging trend in the experience earnings profiles. Still, wage differences between natives and immigrants remain. They are particularly noticeable for highly skilled immigrants, the group needed most in Germany's skill intensive labor market. Separate estimations for immigrant subgroups confirm the general validity of the results.
Keywords: F22; J31; J61; 330; international migration; wage differentials; assimilation; longitudinal data